Aortic elongation part II: the risk of acute type A aortic dissection. Issue 21 (28th March 2018) - Heuts, Samuel; Adriaans, Bouke P; Gerretsen, Suzanne; Natour, Ehsan; Vos, Rein; Cheriex, Emile C; Crijns, Harry J G M; Wildberger, Joachim E; Maessen, Jos G; Schalla, Simon; Sardari Nia, Peyman
Abstract : Objectives: Prophylactic surgery for prevention of acute type A aortic dissection (ATAAD) is reserved for patients with an ascending aortic aneurysm ≥55 mm. Identification of additional risk predictors is warranted since over 70% of patients presenting with ATAAD have a non-dilated aorta or an aneurysm that would not have met the diameter criterion for preventative surgery. Aim of the study was to evaluate ascending aortic elongation as a risk factor for ATAAD and to compare aortic lengths between ATAAD patients and healthy controls. Methods: Aortic lengths and diameters of ATAAD patients were measured on three-dimensional modelled computed tomography and adjusted to predissection dimensions in this cross-sectional single-centre study. Logistic regression was used to evaluate the relation between ATAAD and aortic dimensions. Lengths of different aortic segments were compared with a healthy control group using propensity score matching. Results: Two-hundred and fifty patients were included in the study (ATAAD, n=40; controls, n=210). Ascending aortic length and diameter proved to be independent predictors for ATAAD (OR=5.3, CI 2.5 to 11.4, p<0.001 and OR=8.6, CI 2.4 to 31.0, p=0.001). Eighty patients were matched based on propensity scores (ATAAD n=40, controls n=40). The ascending aorta was longer and more dilated in ATAAD patients compared with healthy controls (78.6±8.8 mm vs 68.9±7.2 mm, p<0.001, 34.4 mm ±3.2. vs 39.4 mm ±5.7, p<0.001, respectively). No differences were found in lengths of the aortic arch and descending aorta. Conclusions: Ascending aortic length could serve as an independent predictor for ATAAD. Future studies addressing indications for prophylactic surgery should also investigate aortic length.